Student Nomination System for FSKTM - Harun, Halwanie; Muhaini Othman, (Applied Information Technology And Computer Science, 2024)
The Student Nomination System is a technology-driven system designed to simplify and improve the process of nominating students for various awards or recognitions within a learning environment. By offering a systematic and efficient methodology, this system manages the shortcomings of traditional nomination procedures. The abstract introduces and describes the key stakeholders involved, emphasizing the use of technology to promote reliability and efficiency. The projected benefits include improved efficiency, fewer mistakes, and an overall improvement in the nomination process. This abstract presents a brief introduction of the Student Nomination System, emphasizing its importance in improving student recognition within the educational system.